2021
DOI: 10.1186/s12913-021-06168-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and diabetes self-management: assessing stakeholder perspectives from health centers in Northern Mexico

Abstract: Background People living with diabetes have an increased risk of developing mental health issues. Mexico has observed a high prevalence of people living with diabetes suffering from mental health issues, such as anxiety and depression. Self-management programs have demonstrated promise in helping participants address and prevent not only physiological health complications but mental health issues as well. This qualitative study aimed to understand the mental health benefits of a diabetes self-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…56 David O. Garcia and colleagues have found that Hispanic men (and women) with diabetes reported a desire for greater family inclusion in their diabetes self-care programs to help support them in establishing healthy behaviors. 59 They have also shown that health messages using fear appeals as well as those reflecting a more positive masculinity were both effective approaches to engage Hispanic males in research and preventive and treatment efforts. 60 Therefore, it is important to consider the variation across populations, groups, and among individuals that may exist within older men's frameworks and experiences of masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…56 David O. Garcia and colleagues have found that Hispanic men (and women) with diabetes reported a desire for greater family inclusion in their diabetes self-care programs to help support them in establishing healthy behaviors. 59 They have also shown that health messages using fear appeals as well as those reflecting a more positive masculinity were both effective approaches to engage Hispanic males in research and preventive and treatment efforts. 60 Therefore, it is important to consider the variation across populations, groups, and among individuals that may exist within older men's frameworks and experiences of masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case despite it being well known that individuals with diabetes are at an increased risk of suffering from mental health problems including anxiety, depression and eating disorders which can lead to poor disease management and reduced compliance with diabetes treatment. 33 , 34 Secondly, there were no studies undertaken in Australia, despite the growing prevalence of diabetes in Australia and the excessive level of burden diabetes places on the Australian health‐ care system. 13 , 35 Thirdly, there is a lack of studies involving diabetes‐specific interventions specifically targeted at reducing diabetes‐specific readmissions rather than overall readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there is a lack of interventions that addressed the psycho‐social factors of individuals living with diabetes. This is the case despite it being well known that individuals with diabetes are at an increased risk of suffering from mental health problems including anxiety, depression and eating disorders which can lead to poor disease management and reduced compliance with diabetes treatment 33,34 . Secondly, there were no studies undertaken in Australia, despite the growing prevalence of diabetes in Australia and the excessive level of burden diabetes places on the Australian health‐ care system 13,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Standards for Reporting Implementation Studies: the StaRI checklist for completion was used a guideline to transparently report on the study in its entirety ( 31 ). Qualitative data on feedback of patient participants surrounding their experience, benefits with MSD, along with opportunities from improvement, facilitators, and barriers have been previously published ( 16 , 32 ). In this manuscript, we focus more generally on reporting the moderating factors that may impact scaling an intervention within an LMIC health system.…”
Section: Methodsmentioning
confidence: 99%